Peran Pengetahuan Dan Sikap Ibu Balita Terhadap Kepatuhan Kunjungan Ke Posyandu Di Wilayah Kerja Puskesmas Jabung - Ratna Roesardhyati; Panche Tri Ambulan Sari (Politeknik Karya Husada, 2026)
Background: Integrated health posts (Posyandu) are community-based health services that play an important role in monitoring child growth and development. The effectiveness of Posyandu largely depends on mothers’ adherence to regular visits. Maternal knowledge and attitudes are predisposing factors that may influence this health behavior. This study aimed to analyze the role of maternal knowledge and attitudes in adherence to Posyandu visits among mothers of under-five children in the working area of Jabung Primary Health Center. Methods: This analytical quantitative study employed a cross-sectional design and was conducted from April to May 2026 in the working area of Jabung Primary Health Center, Malang Regency, Indonesia. The study population consisted of 60 mothers with under-five children who were registered as active Posyandu participants. All eligible mothers were included using total sampling. Knowledge and attitudes were assessed using structured questionnaires, while adherence data were obtained from Posyandu attendance records. Data were analyzed using the Chi-square test with a significance level of 0.05. Results: Most respondents had good knowledge (75.0%), positive attitudes (75.0%), and were adherent to Posyandu visits (86.7%). Maternal knowledge was significantly associated with adherence to Posyandu visits (p = 0.016). Maternal attitudes were also significantly associated with adherence to Posyandu visits (p = 0.014). Conclusion: Maternal knowledge and attitudes were significantly associated with adherence to Posyandu visits. Strengthening health education and promoting positive attitudes may improve mothers’ participation in community-based child health services. Keywords: adherence, attitudes, knowledge, mothers of under-five children, Posyandu.